2016
DOI: 10.1007/s10518-016-9960-1
|View full text |Cite
|
Sign up to set email alerts
|

A geolithological approach to seismic site classification: an application to the Molise Region (Italy)

Abstract: Seismic site classification is a critical issue in order to reliably predict seismic ground motion parameters for the development of microzonation maps and site-specific hazard studies, addressed to territorial planning, real-time generation of shaking maps, and seismic design of engineering structures. The equivalent shear wave velocity through the topmost 30 m (V-S30) is commonly assumed as the reference parameter to provide practical site classifications. Different approaches aimed at expressing local site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Thus, the lithological zone-based geospatial approach is appropriate for large-scale area without geotechnical investigation. For example, the damage distribution observed in the region clearly demonstrates the effect of local site conditions and soil amplification arising from the geological and geotechnical factors [54]. In addition, the inhomogeneities of the geomorphological and geological in Seoul area influence the site-specific variation of site effects and correlations between geotechnical dynamic properties and lithological category.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, the lithological zone-based geospatial approach is appropriate for large-scale area without geotechnical investigation. For example, the damage distribution observed in the region clearly demonstrates the effect of local site conditions and soil amplification arising from the geological and geotechnical factors [54]. In addition, the inhomogeneities of the geomorphological and geological in Seoul area influence the site-specific variation of site effects and correlations between geotechnical dynamic properties and lithological category.…”
Section: Discussionmentioning
confidence: 90%
“…The V S 30 map estimates are also freely available on the USGS website (USGS) worldwide. Several studies have also attempted to correlate V S,30 with geological units (e.g., Forte et al 2017), which are again available via geological maps at various scales for the globe via the One Geology portal (ONEGEO).…”
Section: Soil Profilementioning
confidence: 99%
“…To account for stratigraphic amplification effects at a small scale, Eurocode 8 seismic soil classes are attributed to lithologic units. This is done according to the suggestions provided by Forte et al (2017) for a comparable geo-lithological setting and is reported in Table 4.…”
Section: Site Effects For the Surveyed Buildingsmentioning
confidence: 99%